2018
DOI: 10.1158/1078-0432.ccr-17-2483
|View full text |Cite
|
Sign up to set email alerts
|

The RNA-binding Protein MEX3B Mediates Resistance to Cancer Immunotherapy by Downregulating HLA-A Expression

Abstract: Cancer immunotherapy has shown promising clinical outcomes in many patients. However, some patients still fail to respond, and new strategies are needed to overcome resistance. The purpose of this study was to identify novel genes and understand the mechanisms that confer resistance to cancer immunotherapy. To identify genes mediating resistance to T-cell killing, we performed an open reading frame (ORF) screen of a kinome library to study whether overexpression of a gene in patient-derived melanoma cells coul… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
72
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(72 citation statements)
references
References 30 publications
0
72
0
Order By: Relevance
“…32 In melanoma, Huang et al identified that MEX3B decreased the susceptibility of cancer immunotherapy by targeting HLA-A. 33 Therefore, exploring the precise roles of In summary, this study first characterized the frequent downregulation of SORBS2 in HCC and showed the antitumour function of SORBS2 on the malignant phenotypes of HCC cells, including cell proliferation, migration, invasion, cell cycle progression and EMT both in vitro and in vivo. We further elucidated the underlying molecular mechanism by which SORBS2 stabilized RORA mRNA by binding with its 3′UTR.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…32 In melanoma, Huang et al identified that MEX3B decreased the susceptibility of cancer immunotherapy by targeting HLA-A. 33 Therefore, exploring the precise roles of In summary, this study first characterized the frequent downregulation of SORBS2 in HCC and showed the antitumour function of SORBS2 on the malignant phenotypes of HCC cells, including cell proliferation, migration, invasion, cell cycle progression and EMT both in vitro and in vivo. We further elucidated the underlying molecular mechanism by which SORBS2 stabilized RORA mRNA by binding with its 3′UTR.…”
Section: Discussionmentioning
confidence: 88%
“…Chen et al showed that ROD1 regulated transcription and was required for defining AID‐loading sites to mediate antibody class switching with a PTBP3 deletion in mammalian genomes . In melanoma, Huang et al identified that MEX3B decreased the susceptibility of cancer immunotherapy by targeting HLA‐A . Therefore, exploring the precise roles of SORBS2 during HCC tumourigenesis may help to open novel avenues for the pathogenesis and treatment of HCC.…”
Section: Discussionmentioning
confidence: 99%
“…RNA-binding protein MEX3B was identified as a candidate protein whose overexpression in melanoma cells decreased their susceptibility to killing by autologous TIL in vitro suggesting that it mediates resistance to cancer immunotherapy. Overexpression of MEX3B in melanoma cells decreased IFN-γ release by autologous TILs and downregulated HLA-A expression [32]. Downregulation of HLA-A expression by MEX3B is a novel mechanism for tumor cells to evade attack by T cells.…”
Section: Intrinsic Tumor Genomic and Metabolic Factors Leading To Immmentioning
confidence: 99%
“…HLA class I loss has been shown to prevent continuous T cell recognition in a human melanoma model [154]. HLA-A down-regulation is mediated e.g., by the RNA-binding protein MEX3B [155], by loss of function mutations in the genes encoding the interferon-receptor associated Janus kinase 1 (JAK1) or Janus kinase 2 (JAK2) [156][157][158] or by truncating mutations in the gene encoding β2m [156]. A major impact of HLA class I genotype on clinical outcome with ICI has been corroborated by Chowell et al HLA-I homozygosity in at least one locus was associated with an inferior survival in two independent cancer cohorts undergoing immune-checkpoint blockade and proved as an independent predictor of survival in multivariate analysis.…”
Section: Alterations In the Antigen Presenting Pathwaymentioning
confidence: 99%